A Sensor-Based of Detection Tools To Mitigate People Live in Areas Prone to Landslide - Satryo Budi Utomo; Januar Fery Irawan (UNEJ e-Proceeding, 2016)
Landslide that occurred in the district of Panti, Jember is still leaving concerns the people in the region are affected by the loss of lives and huge material losses. To anticipate the same loss in the future, it is necessary to increase the capacity of community through the establishment of early warning systems in areas prone to landslides locations. The long term goal of this research is to provide emergency response preparedness landslides, so that in the event of micro ground motion at the site of the landslide-prone, the public can readily evacuate to a safe place. By increasing the capacity of the technical aspects, the expected loss and damage caused by landslides can be minimized. The specific objectives are to produce a tool to improve early warning systems through disaster preparedness landslides. The research activity is to make a sensor-based of detection tools of landslides. The working principle of the tool is to know the movement of soil micro-automatically. This tool uses an Arduino to control the working of the entire system, and laser Photodioda sensor used for detecting a shift in the soil due to landslides. From the test results, the voltage available at the time the distance between the laser sensor and the sensor is 50 cm high from the seventh sensor voltage of 0.4 volts whereas when the distance between the laser and the sensor 600 cm is the seventh largest of the voltage sensor at 0:13 volts. This tool can work well in the detection sensor to ground movement.